Research progress in the roles of airway epithelial cells in the pathogenesis of asthma - XU Yinglian; TIAN Jing; ZHANG Xiang; ZHAO Shunying (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Asthma is a common chronic respiratory disease, and as a heterogeneous disease, it is driven by a combination of immune, genetic, and environmental factors and involves multiple cells. In recent years, there has been increasing evidence that airway epithelial cells play a core role in the pathogenesis of asthma. As the first line of defense of the respiratory system against the external environment, airway epithelial cells mainly prevent harmful stimuli from entering through various intercellular connections and remove harmful foreign factors such as allergens and viruses through the mucus and cilia system and the antimicrobial peptides. The airway epithelial barrier can be disrupted when the airway mucosa is exposed to foreign harmful stimuli, and epithelial cells can release various epithelial-derived cytokines that effectively activate dendritic cells and type Ⅱ innate lymphoid cells, thereby triggering a subsequent helper T cell 2 immune cascade response that leads to the development of asthma. In view of these roles of airway epithelial cells in asthma, targeted therapeutic agents targeting the cytokines from airway epithelial cells such as thymic stromal lymphopoietin, are gradually coming into clinical use. This article reviews the role of airway epithelial cells in the pathogenesis of asthma and the future clinical applications of therapies targeting airway epithelial cells as potential targets.